Hubungan Antropometri Ibu Hamil (Berat Badan, Lingkar Atas, Tinggi Fundus Uteri) dengan Reflek Fisiologi Bayi Baru Lahir Normal - Halimatussakdiah Halimatussakdiah; Ampera Miko (AcTion: Aceh Nutrition Journal, 2016)
Maternal Mortality is mostly caused by bleeding (32 %), hypertension during pregnancy (25 %). Infection (5 %), long parturition  5 %),  and chronic energy deficiency (27.66 %). The objective of this research was to find out of correlation Between Maternal  Anthropometry  (Body Weight, Mid Upper Arm Circumference, Fundal Height) And Reflex physiology Of Normal Newborn Babies In delivery room  of Regional Public Hospital Of Meuraxa Banda  Aceh. The research was conducted from September 4 to September 22, 2016. The descriptive  correlation design with cross sectional study approach was used in this research. There were thirty  research sample that were chosen by using accidental sampling method. The result of this research indicated that were was  no correlation between body Weight of pregnant woman with reflex physiology of their normal Newborn Babies In Delivery Room  Of Regional Public Hospital of Meuraxa Banda  Aceh (p Value 0.174). There was a correlation Between Mid Upper Arm Circumference (MUAC) of pregnant women with reflex physiology of their normal Newborn Babies (p Value 0.020). There was also  a correlation between fundal height with reflex physiology of their normal Newborn Babies (p Value 0.000). Based on those result, it is suggest that the pregnant women should pay nurse attention to their health by doing regular check -ups during  pregnancy in order to prevent any complication. It is also suggested that the health worker keep enhancing the medical service, such us the measurement of body weight, MUAC and fundal height. Keywords: Anthropometry, reflex physiology, normal newborn babies